Morphology of the prothorax and procoxa in the New World Cryptocephalini (Coleoptera: Chrysomelidae: Cryptocephalinae) - Chamorro-Lacayo, Maria Lourdes; Konstantinov, Alexander S. (Zootaxa, 2004)
The comparative morphology of the prothorax and procoxae of New World Cryptocephalini was studied based on representatives of 11 of the 13 genera of the tribe. This study revealed a set of characters of obvious diagnostic and possible phylogenetic value supporting the currently accepted generic classification and two subtribes instead of the three currently recognized. Two general typesof prothoracies were found, the first occurring in Cryptocephalina and Monachulina and the second in Pachybrachina. Previously undescribed for Polyphaga, a monocondylic joint between the coxa and trochantin, was found in all the genera studied. Possible movement of the trochanter, including the transfer of advance movement into rotation, is described and illustrated.